2019
DOI: 10.1098/rsbl.2019.0436
|View full text |Cite
|
Sign up to set email alerts
|

Social spider webs harbour largely consistent bacterial communities across broad spatial scales

Abstract: Social animals that live in domiciles constructed from biomaterials may facilitate microbial growth. Spider webs are one of the most conspicuous biomaterials in nature, yet almost nothing is known about the potential for webs to harbour microbes, even in social spiders that live in dense, long-term aggregations. Here, we tested whether the dominant bacteria present in social spider webs vary across sampling localities and whether the more permanent retreat web harbours compositionally distinct microbes from th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Each of these factors has the potential to contribute to increased fungal outbreaks observed at wet sites. Recent metagenomic data from the webs, nests, and cuticles of S. dumicola confirm that microbial transmission from prey to spiders is common (Keiser et al 2019). Furthermore, prior observations of S. dumicola colonies infected by fungus note that individuals "became lethargic and died" (Henschel 1998), indicating that fungal infection can lead to the mortality of these spiders.…”
Section: Discussionmentioning
confidence: 95%
“…Each of these factors has the potential to contribute to increased fungal outbreaks observed at wet sites. Recent metagenomic data from the webs, nests, and cuticles of S. dumicola confirm that microbial transmission from prey to spiders is common (Keiser et al 2019). Furthermore, prior observations of S. dumicola colonies infected by fungus note that individuals "became lethargic and died" (Henschel 1998), indicating that fungal infection can lead to the mortality of these spiders.…”
Section: Discussionmentioning
confidence: 95%
“…The genus Stegodyphus Simon, 1873, in which sociality has evolved three times independently, has become a powerful test system for questions regarding the microbial communities of social spiders and the nests in which they reside. Keiser et al (2019) showed that the silken retreats and capture webs of S. dumicola harbor highly consistent bacterial communities, even from colonies collected hundreds of kilometers apart. Busck et al (2020) published a monumental paper characterizing distinct but overlapping microbial communities associated with all three social Stegodyphus spp.…”
Section: Spider-parasite Ecologymentioning
confidence: 99%
“…Free‐living symbionts are not expected in the core microbiome of social spiders (Busck et al, 2022). The nest microbiome of social spiders differs markedly from the spider microbiome (entire body) (Nazipi, Elberg, et al, 2021), while some overlap in the microbiomes is detected when comparing the spider cuticle microbiome with that of silk from the capture web and nest (Keiser et al, 2019). (b) The experimental design to test stochastic effects on microbiome composition in the establishment of new groups: each of four spider nests collected in the field was split into 15 single spiders, 5 groups of 3 spiders, and 5 groups of 10 spiders.…”
Section: Introductionmentioning
confidence: 99%